Evidence of purchasing power parity from Asean data (Kewujudan pariti kuasa beli daripada data negara-negara Asean) - Hamizun Ismail (Penerbit Universiti Kebangsaan Malaysia, 2011)
﻿Purchasing power parity (PPP) is a theory of long-term equilibrium exchange rates based on relative price levels of two countries. The concept is based on the law of one price; the idea that in the absence of transaction costs, identical goods will have the same price in different markets. PPP exchange rate (the "real exchange rate") fluctuations are mostly due to different rates of inflation between the two economies. Aside from this volatility, consistent deviations of the market and PPP exchange rates are observed. In this study, the PPP hypothesis is examined on a sample of six ASEAN members, namely Indonesia, Malaysia, Myanmar, Philippine, Singapore and Thailand. Specifically, the paper discusses the restricted model for PPP, and briefly describes the derivation of PPP models in cointegrating form and in dynamic error-correction (DECM) form. The results are mixed; the cointegration approach seems to have some advantage over the DECM approach. Nevertheless, assuming that the results fairly represent the ASEAN economies, the evidence in favor of PPP is an early indication of the integration in financial and goods markets within the South-East Asia region.